Fenomena Black Campaign dalam Pemilihan Kepala Daerah 2015 - Tuti Turistiati, Ade (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2016)
Numbers of artists who are involved in political activities in Indonesia are increasing. The relationship between artists and politicians can be complementary. In general, the artists tend to contribute more to boost votes in the elections, including in local elections of district heads (Pilkada) 2015.  However, in a mass mobilization, issues of black campaign are inevitable. This paper is a descriptive study about black campaign against the candidate for Vice Mayor of Palu, Sigit Purnomo Said Syamsuddin, Ungu band vocalist known as Pasha.  Mass media play an important role in spreading black campaign.  In fact, now many voters are an obstinate audience.  They are quite selective in anticipating the black campaign.